A Q-based approach to clausal ellipsis: Deriving the preposition stranding and island sensitivity generalisations without movement. Issue 1 (23rd January 2019) - Griffiths, James
Abstract : This paper argues that the meaning of a clausal ellipsis site can only be recovered from a syntactically derived question, regardless of whether this question is explicitly uttered or is merely pragmatically inferred. This entails that the meaning of a clausal ellipsis site cannot be recovered from an inferred question q in a language L if q is syntactically ill-formed in L. I demonstrate that this restriction on recoverability can account for Merchant's (2001 ; 2004 ) Preposition-Stranding Generalisation and for the observation that fragments appear to be sensitive to syntactic islands (Merchant 2004 ; Abels 2011 ; Barros et al. 2014 ; 2015 ) without any mention of whether remnants of clausal ellipsis themselves undergo movement. Because there is no need to stipulate that remnants themselves undergo (often exceptional) movement under this approach, a theory of clausal ellipsis modelled on Cable's (2010 ) Q-based analysis of wh -questions is developed that permits non-pronunciation "around" designated phrases. This approach is shown to be preferred on many occasions to the predominant movement-based analysis (Merchant 2004 ), which is too restrictive and must frequently resort to the notion of ellipsis repair .